One‐Pot Pseudo Five Component Synthesis of Biologically Relevant 1, 2, 6‐Triaryl‐4‐arylamino‐piperidine‐3‐ene‐3‐ carboxylates: A Decade Update. Issue 34 (13th September 2018) - Kaur, Gurpreet; Devi, Mamta; Kumari, Anjana; Devi, Rekha; Banerjee, Bubun
Abstract: Piperidines, an important class of N ‐heterocycles, are very common in naturally occurring bioactive compounds. Recently, functionalized piperidines, specifically, 1, 2, 6‐triaryl‐4‐arylamino‐piperidine‐3‐ene‐3‐carboxylates have drawn considerable attention due to its diverse pharmacological efficacies that include anti‐cancer, anti‐microbial, anti‐oxidant, anti‐fungal, anti‐inflammatory and acetylcholinesterase (AChE) inhibitory activities. As a result, during the last decade, a number of methods reported for the synthesis of 1, 2, 6‐triaryl‐4‐arylamino‐piperidine‐3‐ene‐3‐carboxylates via one‐pot pseudo five‐component reactions of aromatic aldehydes, anilines and β‐keto esters under various reaction conditions. The present review deals with the ''up to date" developments on the synthesis of 1, 2, 6‐triaryl‐4‐arylamino‐piperidine‐3‐ene‐3‐carboxylates reported so far. Abstract : The present review deals with the recent developments on the synthesis of biologically promising 1, 2, 6‐triaryl‐4‐arylamino‐piperidine‐3‐ene‐3‐carboxylate derivatives via the reactions of two equivalents of aromatic aldehydes, two equivalents of amines and one equivalent of alkyl acetoacetate under various reaction conditions. For this pseudo five‐component reaction the catalytic applicability of a number of metal catalysts, organocatalysts, ionic liquids, solid supported catalysts, surfactants is discussed.